2004
DOI: 10.1590/s0034-89102004000500016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pathogens from periodontal lesions

Abstract: ObjectiveTo comparatively detect A. actinomycetemcomitans and F. nucleatum from periodontal and healthy sites. Methods Subgingival clinical samples from 50 periodontitis adult patients and 50 healthy subjects were analyzed. Both organisms were isolated using a trypticase soy agarbacitracin-vancomycin (TSBV) medium and detected by PCR. Conventional biochemical tests were used for bacteria identification. Results A. actinomycetemcomitans and F. nucleatum were isolated in 18% and 20% of the patients, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In this study, by culture, A. actinomycetemcomitans was isolated from 18% of the periodontal patients and 2% of the healthy subjects, in accordance with Asikainen et al (1) and Malheiros and AvilaCampos (22). Moreover, studies have shown that the occurrence of A. actinomycetemcomitans varied from 20% to 80% in adult periodontitis patients (3,22,33). On the other hand, by using a PCR method, this microorganism was detected in 44% of the periodontal patients, and in 16% of the healthy subjects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, by culture, A. actinomycetemcomitans was isolated from 18% of the periodontal patients and 2% of the healthy subjects, in accordance with Asikainen et al (1) and Malheiros and AvilaCampos (22). Moreover, studies have shown that the occurrence of A. actinomycetemcomitans varied from 20% to 80% in adult periodontitis patients (3,22,33). On the other hand, by using a PCR method, this microorganism was detected in 44% of the periodontal patients, and in 16% of the healthy subjects.…”
Section: Discussionsupporting
confidence: 87%
“…In healthy subjects, biotypes II, VI and X were observed. Few studies have shown the presence of biotypes in A. actinomycetemcomitans and the biotype II appears to be the most prevalent in Brazilian periodontal patients (3,22).…”
Section: Discussionmentioning
confidence: 99%
“…Those pathogens found in Brazilian patients with periodontal diseases include A. actinomycetemcomitans, P. gingivalis, P. intermedia, T. forsythia, C. rectus, Eikenella corrodens, Treponema denticola, Streptococcus spp., and some others (3,4,6,7,8,9,24,26,32,33,34). In particular, these previous studies focused on the prevalence of periodontal pathogens in diseased subjects representing four different stages of clinical treatment, as follows: (i) before periodontal treatment, (ii) after nonsurgical mechanical therapy (scaling and root planing), (iii) after antibiotic therapy, and (iv) after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of A. actinomycetemcomitans in aggressive periodontitis was found to range between 67% and 80%, with the majority of isolates belonging to biotype X . In chronic periodontitis, the prevalence of A. actinomycetemcomitans periodontitis was 18% with a predominance of biotype II . Leukotoxic strains of A. actinomycetemcomitans (JP2 clone, serotype b) were a common finding in aggressive periodontitis in South America, with a particularly high prevalence in Brazil .…”
Section: Periodontal Microbiology In Latin Americamentioning
confidence: 96%